Concrete-ice abrasion: wear, coefficient of friction and ice consumption - Shamsutdinova, Guzel; Hendriks, Max; Jacobsen, Stefan (Wear, 2018)
Concrete structures in the Arctic offshore are often exposed to drifting ice causing abrasion of concrete surfaces. This paper presents the results of a laboratory study of concrete-ice abrasion. The sawn concrete surfaces (two high-performance concrete mixes and one light weight mix of concrete) were exposed to sliding fresh-water ice under 1MPa pressure for 3km of sliding distance. The effect of concrete compressive strength, ice consumption, and the coefficient of friction on abrasion was studied simultaneously. The results show a low abrasion of concrete, the maximum abrasion depth (0.35mm) after 3km of sliding test was found for the concrete samples with the lowest compressive strength. All tests showed a severe-to-mild wear transition, with the maximum wear rate in the first sliding kilometre. The coefficient of friction was high when ice consumption was high due to ice spallation and pulverization, whereas the coefficient of friction was not directly correlated to the wear. The wear or consumption of the ice (abrasive) was in the order of 30000 – 100000 times that of concrete despite of its strength and stiffness 1 – 10 times lower than that of concrete. acceptedVersion © 2018. This is the authors’ accepted and refereed manuscript to the article. Locked until 14.9.2020 due to copyright restrictions. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/